1980
DOI: 10.1159/000241367
|View full text |Cite
|
Sign up to set email alerts
|

Cortisone and Cortisol in Maternal and Fetal Blood and in Amniotic Fluid during the Final Ten Days of Gestation in the Rabbit

Abstract: We have used instant thin-layer chromatography and radioimmunoassay to measure the concentrations of total cortisone (E) and cortisol (F) in the fetal and maternal compartments of the rabbit. The concentration of F in fetal blood increased markedly at day 25; this is just prior to the rapid increase in the surfactant phospholipids in lung tissue in this species. This increase coincided with a peak in the concentration of E and F in the maternal blood and may reflect the maternal levels. There was no ‘surge’ in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…Mean plasma concentrations of glucagon and glucocorticoids were comparable to those observed in earlier investigations [17,28,29]. There was evidence from the 26 and 28 day age group that concentrations of glucagon were negatively correlated with fetal size, a finding consistent with observations on normal and growth-retarded guinea pigs [30].…”
Section: Discussionsupporting
confidence: 86%
“…Mean plasma concentrations of glucagon and glucocorticoids were comparable to those observed in earlier investigations [17,28,29]. There was evidence from the 26 and 28 day age group that concentrations of glucagon were negatively correlated with fetal size, a finding consistent with observations on normal and growth-retarded guinea pigs [30].…”
Section: Discussionsupporting
confidence: 86%
“…We have also found that whereas the fetal liver favoured reduction, the kidneys tended to oxidise E [unpublished observations]; the rabbit is sim ilar to the human fetus in this respect [12], Hence the final balance between 3H-E and 3H-F in the fetal blood would reflect the 11 (3-oxidase/reductase activities of the different tissues and their relative blood flows. In fact, we previously showed that at day 25 of gesta tion in the rabbit, the concentration of F in fetal blood greatly exceeds that of E [1], Marked species differences exist between the ability of tissues to interconvert E and F. Cer tainly in the case of the lung, the rat and rab bit readily reduce E to F [9,14,15], whereas the human fetus shows a large oxidase activ ity [12].…”
Section: Discussionmentioning
confidence: 99%
“…This involved manip ulation of both the uterus and the fetus with the possible associated risk of fetal hypother mia. Furthermore, the dose of radiolabeled steroid injected far exceeded a tracer amount, varying between 20 and 170% of the endoge nous E or F present in the amniotic compart ment at the time [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations